Crescimento urbano e seus impactos no sistema de drenagem de uma bacia em Natal/RN - Gurgel, Geórgia Moreira (2016)
The uncontrolled growth of most Brazilian cities is not accompanied by the development of urban infrastructure. With increasing soil sealing, runoff and decreased infiltration volume, impacts on water resources and on population of the areas affected by urban growth are inevitable. This study aims to evaluate the use and occupation of a watershed and analyze the drainage system in order to control the impact using tools to integrate urban development with the drainage of rainwater in an important watershed in the Natal City, Rio Grande do Norte State. The study involved the characterization of the basin XII.4 on the land use and occupation, for the years 2005 and 2014. With the application of SWMM model was possible to analyze the impacts caused by the urbanization process in the existing drainage system, showing the two years analyzed have their areas very close to percentage saturation of impervious areas. Although the region is still predominantly single family residential, suffers increasing verticalization of mainly commercial buildings. The drainage system is inefficient for the area's needs by the year 2005. The drainage system was also tested for four variations of land use by developing scenarios. Scenario 1 is related to the year 2014, considered current. Scenario 2 was adopted the maximum rate of 80% for land use, allowed for the Natal City. Scenario 3 gives the critical condition of land use, with the area 100% impervious. Scenario 4 is applied to the existence of LID (Low Impact Device). The scenarios analysis showed that all indicate deficiency at some point of the drainage system as a result of the high degree of occupation of the area that generate higher flows than the initial drainage system capacity. With the study it became clear that the adoption of non-structural tools are effective in reducing flooding and improving the drainage system capacity.